IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS QUIZ WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS III SDN KLENANG LOR I - Wiwin Wulandari; Didit Yulian Kasdriyanto; Ryzca Siti Qomariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low cognitive learning outcomes of third-grade students at SDN Klenang Lor I in the Pancasila Education subject, particularly the topic of rules at home and school. Students were less active during learning, the teaching methods did not meet their learning needs, and there was minimal use of engaging learning media. In addition, the learning process was still teacher-centered, which hindered student participation. This study employed Classroom Action Research (CAR), aimed at increasing student engagement and improving learning outcomes. The CAR method consists of four stages: planning, implementation, observation, and reflection. The research was conducted in two cycles, each consisting of two meetings. The subjects were 19 third-grade students, comprising 10 boys and 9 girls. The study took place from February 18 to February 22, 2025. In the first cycle, 13 out of 19 students achieved learning mastery (68.42%). After improvements were made in the second cycle through the application of cooperative learning methods and the use of a game-based learning media called “Quiz Wordwall,” the number of students achieving mastery increased to 18 out of 19 (94.73%). This improvement demonstrates that the use of interactive media tailored to students’ learning needs can enhance cognitive learning outcomes. Therefore, the application of cooperative learning methods and game-based educational media proved effective in improving the learning outcomes of third-grade students at SDN Klenang Lor I.